The The effect of distance learning on the diversity of moral values of junior high school students in the district of Turi - Durrotun Nafisah; Ahmat marzuki; Abd Ghofur (Journal of diversity in learning (JDIL), 2021)
The COVID-19 pandemic has resulted in learning that was previously carried out face-to-face into distance learning (PJJ). This causes students to get used to using gadgets for other activities, so that moral values ​​in the form of self-discipline and responsibility of students can be controlled directly, while during distance learning the teacher has difficulty controlling it optimally. This study aims to determine whether there is an effect of distance learning on the moral values ​​of SMPN 1 Turi students. This study uses a quantitative method, the sample used by the researcher is a random sample of 32 respondents. The test technique uses simple linear regression analysis, the results obtained from the calculation of t count with t table with an error rate of 5%, it is known that t count is 3.858 greater than t table 2.042 so it can be concluded that H0 is rejected and H1 is accepted. There is an influence between distance learning on moral values.